2011
DOI: 10.1007/s12369-011-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Hand-Arm Manipulation Based on Tri-axial Tactile Data

Abstract: Tactile sensing ability is important for social robots, which perform daily work instead of persons. The authors have developed a three-axis tactile sensor based on an optical measurement method. Since our optical three-axis tactile sensor can measure distributed tri-axial tactile data, a robot equipped with the tactile sensors can detect not only grasping force but also slippage from its hands. In this paper, the authors have two objectives: one of them is evaluation of the three-axis tactile sensor in actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Figure 12 and 13 show changes in the normal force distribution of fingers #1 and #2, respectively and Fig. 14 shows the time derivative of the tangential force of the specific elements, which indicates slippage (Ohka et al, 2012). The element numbers in Fig.…”
Section: Position and Force Datamentioning
confidence: 99%
“…Figure 12 and 13 show changes in the normal force distribution of fingers #1 and #2, respectively and Fig. 14 shows the time derivative of the tangential force of the specific elements, which indicates slippage (Ohka et al, 2012). The element numbers in Fig.…”
Section: Position and Force Datamentioning
confidence: 99%
“…In our laboratory, an articulated hand-arm robot is developed to achieve the aforementioned intelligent tasks [3]. Since we used the hand part of the robot in this study, it is shown in Fig.…”
Section: Robotic Hand-armmentioning
confidence: 99%
“…On the other hand, implementation of program module to induce behaviour of robot arm was introduced [22][23][24][25]. They use tri-axial tactile information acquired by the two-hand-arm robot to measure an object with direct touch and it obtain the real scale of geometrical data.…”
Section: Current Research On Hand Function Rehabilitationmentioning
confidence: 99%